Implementation of the Contextual Teaching and Learning Approach in Islamic Education Learning at Mts Miftahul Huda - Muhammad Kafnun Kafi; Zaenal Abidin; Lilis Fauziah Balgis; Agung Muttaqien (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2025)
The Contextual Teaching and Learning approach is one of the approaches implemented at MTs Miftahul Huda, a private school located in a village. Many factors, especially religion, influence students, so teachers use this approach to make it easier for students to understand and implement learning materials. This study aims to determine the application of the contextual approach in Islamic studies learning and the factors that influence it. The method used is a descriptive qualitative case study, with the principal, vice principal for curriculum, Islamic religious teachers, and students as data sources. The results show that the implementation of the contextual approach at MTs Miftahul Huda is running well. Islamic religious teachers have implemented this approach according to its aspects and components. Factors that support the successful implementation include a supportive classroom atmosphere, student enthusiasm in learning, and the availability of learning media. However, there are several inhibiting factors, such as the persistence of teachers who do not understand the theory of the contextual approach, unstable students' cognitive aspects, and limited learning time.